Subordinated Inclusion: Population Sorting Technologies as Digital Confinement in the United States, China, and Israel - Ketter, Karissa; Byler, Darren (Surveillance & Society, 2025)
This article considers recent developments in population level watchlists that emerge from racialized economies. By demonstrating how they develop over time and in relation to population sorting technologies, it argues that these tools are increasingly used to include and control racialized groups in the same digitally enclosed space as protected citizens. This structured process stems from automation-assisted surveillance systems built by corporate state contractors such as BI Incorporated, HikVision, and Twentsche Kabel Holding Security Solutions. Building on the scholarship on the social life of surveillance and social sorting, it argues that automation assisted sorting of populations—asylum seekers in the US, Uyghurs in China, and Palestinians in Israeli controlled spaces—into categories of broadly defined color-coded threats produces population levels of control that deeply inhibit the autonomy of categorized individuals. Since threat production technology produces forms of automated racialization, by turning faces and behaviors into objects of data collection and analysis that are correlated to threat perception, it results in forms of subordinated inclusion that appear permanently foreclosed.